Fluorescein Angiography of Persistent Incomplete Vascularization of the Retina After Bevacizumab Therapy in Retinopathy of Prematurity. (September 2019) - Lin, Xihui; Patel, Sagar B.; Zhang, Alice Y.; Brill, Daniel A.; Le, Kim H.; He, Yu-Guang
Purpose: This study evaluates the vascular development of premature infants at 50 weeks postconception after treatment with intravitreal bevacizumab for type 1 retinopathy of prematurity (ROP). Methods: A retrospective case series was conducted on type 1 ROP neonates with a high risk of general anesthesia complications. Patients were treated with bevacizumab between February 2013 and February 2016. At 50 weeks' gestational age, all patients were imaged with RetCam (Clarity Medical Systems, Inc) fundus photographs and widefield fluorescein angiography (FA). Results: There were 4 boys and 7 girls with an average gestational age of 24.8 weeks and weight of 734.3 grams at birth. The estimated gestational age at injection was 37.1 weeks. Examination under anesthesia with FA was performed at a mean of 61 weeks posttreatment. Nineteen of 20 eyes (95%) of 11 infants had incomplete vascularization and peripheral nonperfusion on imaging. FA showed new vessels with increased tortuosity, microvascular abnormalities, and leakage past the original ridge. These 19 patients were treated with confluent ablative photocoagulation to the peripheral nonperfused retina. Patients were followed for a mean of 73.3 weeks after birth. None required incisional surgery. Conclusions: Patients with type 1 ROP treated with bevacizumab may have delayed vascularization of the peripheral retina and even late recurrence of active disease. Clinicians should regularly monitor patients after bevacizumab for potential neovascular complications.